2016
DOI: 10.4103/0019-5049.193664
|View full text |Cite
|
Sign up to set email alerts
|

Effect of melatonin on duration of delirium in organophosphorus compound poisoning patients: A double-blind randomised placebo controlled trial

Abstract: Background and Aims:Organophosphate compound poisoning (OPCP) is associated with high incidence of delirium. Melatonin has been tried in the treatment of delirium and has shown a beneficial effect in OPCP. This study was conducted to know the effect of melatonin on duration of delirium and recovery profile in OPCP patients.Methods:Double-blind randomised placebo control trial in which 56 patients of OPCP confirmed by history and syndrome of OPCP with low plasma pseudocholinesterase, aged >18 years and weighing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 30 publications
(36 reference statements)
0
19
0
Order By: Relevance
“…The results of the present meta-analysis indicated that melatonergics were associated with a decreasing incidence of delirium in critically ill patients. Based on the encouraging results of the primary RCTs (10,12,20,22), suggesting that administration of melatonin and melatonin agonists might be a promising medication for the prevention of delirium in at-risk populations, our meta-analysis provided advanced evidence. These encouraging results were considered to be quite reasonable.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The results of the present meta-analysis indicated that melatonergics were associated with a decreasing incidence of delirium in critically ill patients. Based on the encouraging results of the primary RCTs (10,12,20,22), suggesting that administration of melatonin and melatonin agonists might be a promising medication for the prevention of delirium in at-risk populations, our meta-analysis provided advanced evidence. These encouraging results were considered to be quite reasonable.…”
Section: Discussionmentioning
confidence: 99%
“…Ramelteon was administered in the other two (15,22). The subjects of six RCTs (10,13,15,(20)(21)(22) were elderly (mean age, >60 years), whereas they were apparently younger (mean age, <40 years) in the other (12). Table 1 presents the characteristics of the included studies.…”
Section: Study Characteristics and Qualitymentioning
confidence: 99%
See 2 more Smart Citations
“…Twelve trials, [7,11,[16][17][18][19][20][21][22][23][24][25] including 2538 patients, were evaluated and eligible for the meta-analysis. The flow diagram for study inclusion is shown in Figure 1.…”
Section: Study Selection and Study Characteristicsmentioning
confidence: 99%